1994
DOI: 10.1007/bf03158590
|View full text |Cite
|
Sign up to set email alerts
|

Identification by meconia of two egg parasitoids ofThaumetopoea wilkinsoni

Abstract: Baryscapus servadeii (Domo and Ooencyrtus pityocampae (Mercet) were the most frequent egg parasitoids of Thaumetopoea wilkinsoni Taras (Lep.: Thaumetopoeidae) in the Mountains of Lahav, Israel. Their meconia, remaining in the eggs, differ in structure and can be used to determine the annual rate of parasitism without collecting emergent adults. In B. servadeii, diapausing insects can be discriminated fmm non-diapausing ones by their meconia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Many egg parasitoids emerged before sampling of the egg‐batches, but could be identified later through the specific characteristics of their meconia ( Schmidt 1994 ; Tanzen 1995) .…”
Section: Methodsmentioning
confidence: 99%
“…Many egg parasitoids emerged before sampling of the egg‐batches, but could be identified later through the specific characteristics of their meconia ( Schmidt 1994 ; Tanzen 1995) .…”
Section: Methodsmentioning
confidence: 99%
“…A ) Meconium of a Anastatus bifasciatus larva (d), B) Meconium of a Macroneura vesicularis larva (0) , both after diapausing decelopment without remains of the host purpose it was useful to prepare the scheme shown in table 1. In this way emergence could be related to the specific meconia and remains (SCHMIDT and KITT, 1994) and the meconia of two further egg parasitoids could be identified. We found that many egg parasitoids emerged in the fall of the same year, but not much later after the hatching of the caterpillars (SCHMIDT, 1988).…”
Section: Parasitoid Impactmentioning
confidence: 99%
“…It is possible to determine the impact of parasitism and mortality rate at any time in the year. SCHMIDT and KITT (1994) studied and described the differences in the meconia of 0. piiyocumpue and B. serradeii. In each host egg, 'The research conducted w a s supported by the Government of Lower Saxony.…”
Section: Introductionmentioning
confidence: 99%
“…The meconium can often be clearly seen within the emptied host egg through the exit hole or by dissection if necessary. The morphological analysis of meconia has previously been proposed for species identification within the parasitoid guild of different agricultural and forest pests (Schmidd and Kitt 1994;Mirchev et al 2004;Sands and Liebregts 2005;El-Heneidy and Adly 2009).…”
Section: Introductionmentioning
confidence: 99%